2018
DOI: 10.4103/ijo.ijo_1446_18
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal artery occlusion

Abstract: The pathogeneses, clinical features, and management of central retinal artery occlusion (CRAO) are discussed. CRAO consists of the following four distinct clinical entities: non-arteritic CRAO (NA-CRAO), transient NA-CRAO, NA-CRAO with cilioretinal artery sparing, and arteritic CRAO. Clinical characteristics, visual outcome, and management very much depend upon the type of CRAO. Contrary to the prevalent belief, spontaneous improvement in both visual acuity and visual fields does occur, mainly during the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 37 publications
2
103
0
1
Order By: Relevance
“…Macular edema in RVO often shows a diurnal variation, with edema being worse in the morning and improving late in the day; this relates to the fact that, during sleep, nocturnal hypotension occurs resulting in a decrease in blood flow and an increase in intravenous pressure and, as a result, an increase in edema [Reviewed by Hayreh] (108,110) .…”
Section: Macular Edemamentioning
confidence: 99%
See 3 more Smart Citations
“…Macular edema in RVO often shows a diurnal variation, with edema being worse in the morning and improving late in the day; this relates to the fact that, during sleep, nocturnal hypotension occurs resulting in a decrease in blood flow and an increase in intravenous pressure and, as a result, an increase in edema [Reviewed by Hayreh] (108,110) .…”
Section: Macular Edemamentioning
confidence: 99%
“…In CRVO, blockage of the main vein draining the retina, the central retinal vein, occurs (74,114) . In this type, the occlusion usually takes place at or behind the laminal cribrosa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SS Hayreh in his landmark study in 1994 concluded that "In FA, the extent of capillary non-perfusion is a reliable criterion to differentiate the two types of CRVO." (14) Abraham C in his study stated that "FA has not only helped in documenting findings but has been a useful aid in choosing and planning patients for photocoagulation." (15) Inflammatory Disorders 8 cases (20%) of inflammatory disorders were analysed.…”
Section: Diabetic Retinopathymentioning
confidence: 99%